Role of PhoPR in the response to stress of Mycobacterium bovis - Garcia, Elizabeth Andrea; Blanco, Federico Carlos; Klepp, Laura Ines; Pazos, Adriana Alejandra; McNeil, Michael; Jackson, Mary; Bigi, Fabiana (Elsevier, 2021)
PhoP is part of the two-component PhoPR system that regulates the expression of virulence genes of Mycobacteria. The goal of this work was to elucidate the role of PhoP in the mechanism that Mycobacterium bovis, the causative agent of bovine tuberculosis, displays upon stress. An analysis of gene expression and acidic growth curves indicated that M. bovis neutralized the external acidic environment by inducing and secreting ammonia. We found that PhoP is essential for ammonia production/secretion and its role in this process seems to be the induction of asparaginase and urease expression. We also demonstrated that the lack of PhoP negatively affected the synthesis of phthiocerol dimycocerosates. This finding is consistent with the role of the lipid anabolism in maintaining the redox environment upon stress in mycobacteria. Altogether the results of this study indicate that PhoP plays an important role in the response mechanisms to stress of M. bovis.